The influence of iron and cobalt on the type II hot corrosion behavior of NiCr model alloys. Issue 7 (19th April 2020) - König, Till; Montero, Xabier; Galetz, Mathias
Abstract: The type II hot corrosion behavior of the alloys NiCr20, NiCr20Co10, and NiCr20Fe10 is investigated at 700°C in synthetic air + 0.5% SO2 for up to 300 hr. Pure Na2 SO4 and a eutectic mixture of MgSO4 –Na2 SO4 are applied as deposits. The kinetics are investigated via dimensional metrology and correlated to the microstructural progression of the corrosion by examining the cross‐sections. All alloys exhibit two‐stage corrosion kinetics, with initially low and subsequently increased metal losses. Independent of the deposit composition, the metal loss after the longest exposure time is increased by the alloying element cobalt, whereas it is decreased for the iron‐containing alloy. All alloys show increased metal losses when exposed to the MgSO4 –Na2 SO4 deposit. The time to the propagation stage is similar for all tests. During the stage of low metal loss, all alloys develop a chromia scale and internal chromium sulfides. When the propagation stage is reached, chromium and nickel can be found along with oxygen and sulfur within the pit. Nickel is dissolved into the deposit, where it precipitates. Abstract : The type II hot corrosion behavior of NiCr20 model alloys with the additional alloying elements, iron and cobalt, is investigated at 700°C in synthetic air + 0.5% SO2 with two different salt deposits. For the cobalt‐containing alloy, an increased metal loss is observed, whereas the iron additions decrease the corrosion attack. The formation of pits and the precipitation of nickel oxides in the salt are observed.